Innovation capability, disruptive technology and SME's performance in Malaysia - Singh, Daljeet Singh Malkeet (2018)
The aim of this study is to examine the relationship between innovation capacity (IC), and firm performance (FP) mediated by disruptive technology (DT) among SMEs within Selangor, Malaysia. The theoretical model is based on the Resource-Based Theory and the Theory of Innovation. To answer the research questions, four hypotheses were formulated. They are; (i) There is a significant relationship between innovative capacity and SMEs performance, (ii) There is a significant relationship between innovative capacity and disruptive technology, (iii) There is a significant relationship between disruptive technology and SMEs performance, (iv) There is a significant relationship between innovative capacity and SMEs performance mediated by disruptive technology. Self-administrated questionnaires were distributed to 800 owner-managers of SMEs in Selangor. A total of 150 firms responded in this study. This study utilised the Partial Least Squares Structural Equation Modelling (PLS-SEM) to establish validity and reliabiliy of measurement model and test the relationships. The results show a positive and significant relationship between innovation capacity and firm performance mediated by disruptive technology. Owner-manager of SMEs should emphasize innovativeness on all four (4) dimensions of innovations to ensure better firm performance. The results of this study also provides a better insight for various stakeholders to further understand the effects of IC and DT on SMEs performance. The study provides empirical evidence for theoretical relationship hypothesized in the research framework and also adds to knowledge on the importance of innovativeness in all aspects of firm’s offering along with adoptation of disruptive technologies in predicting firm performance. The study is confined to firm operating in Selangor. It is recommended that future research should also include other state(s) in Malaysia.